The Effect of Couple-Based Intervention on Marital Satisfaction, psychological Conditions of Mothers and Spouse, and Postpartum Spouse Support - Gemi Rahayu; Heni Dwi Windarwati; Laily Yuliatun (Buletin Penelitian Kesehatan, 2026)
Background: Maternal mental health issues impact not only individuals but also infants, spouses, families, and communities. Therefore, efforts in the prevention and treatment of postpartum maternal mental health problems are essential to support maternal and family well-being. One form of applicable intervention is a couple-based intervention. This study analyzed the effects of couple-based intervention on marital satisfaction, the psychological well-being of mothers and their spouses, and spouse support. Methods: This quasi-experimental design used a control group and pretest-posttest framework. The researchers used a sample of 38 primiparous postpartum mothers and their spouses. The researchers conducted the research in the working area of the Dau Community Health Center in Malang Regency. Some of the applied questionnaires were the ENRICH Marital Satisfaction Scale, the General Health Questionnaire, the Self-Reporting Questionnaire of Minor Psychiatric Disorders, and the Spouse Interaction After Baby Scale. These were all used along with the couple-based intervention. The researchers analyzed the data using paired sample t-tests and independent sample t-tests. Results: The results showed that the couple-based intervention provided a significant difference in the experimental group's marital satisfaction, maternal and partner mental health, and partner support based on the paired t-test (p value <0.05 sig=0.00). On the other hand, the control group, which only received information leaflets, did not show any significant changes (p value> 0.05 sig=0.00). Based on the results of the independent sample t-test, the p value <0.05 sig=0.00 was obtained. This shows a significant difference in the components of marital satisfaction, psychological conditions, and spouse support between the treatment group, after providing the couple-based intervention, and the control group, after receiving standard education through leaflets. Conclusion: The study concluded that couple-based interventions improve marital satisfaction, maternal and spouse psychological well-being, and spouse support. We recommend couple-based interventions as an approach to enhancing Improves the psychological well-being of mothers and spouse.